Sirtuins in kidney homeostasis and disease: where are we now? - Fan, Zhongyu; Wei, Xuejiao; Zhu, Xiaoyu; Du, Yujun (Frontiers in Endocrinology, 2025)
Sirtuins, identified as (NAD+)- dependent class III histone deacetylases, engage in a spectrum of biological functions, encompassing DNA damage repair, oxidative stress, immune modulation, mitochondrial homeostasis, apoptosis and autophagy. Sirtuins play an apoptosis role in regulating cellular operations and overall organism health. Mounting data indicate that dysregulated sirtuin expression is linked to the onset of renal diseases. Effective modulation of sirtuins expression and activity has been shown to improve renal function and attenuate the advancement of kidney diseases. In this review, we present a comprehensive overview of the biological impacts of sirtuins and their molecular targets in regulating renal diseases. Additionally, we detail advancements in elucidating sirtuin roles in the pathophysiology of both chronic and acute renal disorders. We review compounds that modulate sirtuin activity through activation or inhibition, potentially improving outcomes in renal disease. In summary, strategic manipulation of sirtuin activity represents a prospective therapeutic approach for renal diseases.